The pull of the stars [compact disc, unabridged] : a novel - Donoghue, Emma, 1969- (Hachette Audio, 2020)
Dublin, 1918. Ireland is ravaged by war and disease. Nurse Julia Power works in a quarantined maternity ward. Two outsiders step into her world, who she will connect with in unexpected ways.